Correlation and risk factor analysis of multifidus muscle atrophy in degenerative lumbar spondylolisthesis - Zhang, Cong; Sun, Rui; Wu, Xiaotao; Sun, Xiaozhi (Frontiers in Medicine, 2025)
ObjectiveWe evaluated differences in multifidus muscle atrophy (MMA) among patients with degenerative lumbar spondylolisthesis (DLS) across various segments and grades of spondylolisthesis, analysed the correlation between DLS and MMA, identified risk factors contributing to MMA, and provided a clinical reference for the prevention and treatment of MMA.MethodsThis retrospective study analysed data from 213 patients diagnosed with single-segment DLS between September 2020 and January 2022. Participants were categorised into three groups based on the affected spinal segment: L3 (n = 27), L4 (n = 140), and L5 (n = 46). The LCSA/GCSA ratio was calculated to assess the extent of MMA. Differences in MMA and its correlation with DLS severity were analysed across different spondylolisthesis grades. Furthermore, based on the Kjaer classification, patients were stratified into Mild and Severe MMA groups. A multivariate logistic regression analysis was performed to identify risk factors influencing the degree of MMA in DLS patients.ResultsThe LCSA/GCSA ratio at the spondylolisthesis segment was significantly lower than that at the non-spondylolisthesis segment (p < 0.001). When comparing LCSA/GCSA ratios between different grades of lumbar spondylolisthesis (Grade I and II), no statistically significant differences were observed (p > 0.05). In the general population, a strong positive correlation was identified between the degree of MMA and the VAS and ODI scores for low back pain, whereas no significant correlation was found with the VAS score for leg pain. Age, BMI, and osteoporosis demonstrated statistically significant differences between the two groups (p < 0.05). Multivariate logistic regression analysis identified age, BMI, and osteoporosis as significant risk factors for MMA progression in DLS patients (p < 0.05).ConclusionDLS patients exhibit MMA, with more pronounced atrophy at the spondylolisthesis-affected segment. Age, BMI, and osteoporosis are independent risk factors for MMA progression in DLS patients. Clinically, it is crucial to identify and monitor high-risk patients with these factors and implement early preventive and therapeutic interventions to mitigate disease progression.